The effect of e-accounting on the performance of small medium enterprises (SMEs) in Baghdad with internal control system as mediator - Jasim, Ali Mohammed Hussein (Tanjong Malim, 2022)
The effect of e-accounting on the performance of small medium enterprises (SMEs) in Baghdad with internal control system as mediator by Jasim, Ali Mohammed Hussein